Anaerobic digestion of algal biomass for bioenergy production- a feasibility study - Inglesby, Alister Edward (Centre for Bioprocess Engineering Research, 2015)
AD technology is well developed, cost efficient and can be easily implemented in developing countries. Biogas production has become a very topical subject, with many European nations introducing initiatives to increase biogas production. AD of algal biomass was studied in detail during the 1980’s, however, with the current drive toward cleaner technology processes, there has been a renewed interest in the technology. This study investigated the feasibility of using algal biomass as a feedstock for AD.